Sodium-ion battery carbon negative electrode material and preparation method and application thereof
By preparing alumina-coated sodium ion battery carbon anode material, the problems of limited sodium storage capacity and short cycle life of the sodium ion battery anode material in the prior art are solved, and higher crystallinity, conductivity and cycle performance are achieved.
Patent Information
- Application Number
- CN202411597197.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing sodium-ion battery carbon-based negative electrode materials have limited sodium storage capacity, short cycle life, and severe volume expansion during charging and discharging, resulting in electrode powderization.
Alumina-coated alumina coated by mixing coal powder with sodium bicarbonate and then performing hydrothermal treatment in aqueous sodium hydroxide solution to reduce metal impurities, and then mixing with nano-alumina and sodium hydride in an atmosphere of ethylene and inert gas to prepare alumina coated alumina Sodium ion battery carbon anode material.
The crystallinity and conductivity of the carbon anode material of sodium ion battery are improved, the capacity and circulation performance are improved, the cycle life of the battery is extended, and the sodium loss is reduced.
Smart Images

Figure CN119480980A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a sodium ion battery carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Among the existing negative electrode materials for sodium-ion batteries, carbon-based materials are the earliest and most studied negative electrode materials. Graphite has become the most widely used negative electrode material for lithium-ion batteries due to its high volumetric capacity and good cycle performance. However, the capacity of graphite to store sodium is very limited. It is generally believed that it takes a lot of energy for sodium ions with large ionic radius to embed into the graphite layer. Disordered carbon has a low degree of graphitization and a large interlayer spacing, making it a carbon-based material with better performance at present. Carbon materials expand severely in volume during the charge and discharge process, which makes the electrode easily pulverized and has a short cycle life. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sodium ion battery carbon negative electrode material and a preparation method and application thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a carbon negative electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0005] (1) mixing coal powder and sodium bicarbonate, calcining the mixture at 270° C. to 350° C. for 60 to 120 minutes, and cooling the mixture to obtain a mixture A;
[0006] (2) mixing the mixture A in a sodium hydroxide aqueous solution at 65 to 80° C. and stirring to react for 1.5 to 4 hours, collecting the solid mixture B after solid-liquid separation, and the concentration of the sodium hydroxide aqueous solution is not less than 2 mol / L;
[0007] (3) washing the solid mixture B with deionized water until it is neutral, collecting the solid mixture C and drying it;
[0008] (4) After mixing the solid mixture C with nano-alumina and sodium hydride, sintering the mixture in an atmosphere of ethylene and inert gas to obtain a carbon negative electrode material for a sodium ion battery. The maximum sintering temperature is 400-600° C., the insulation time is 4-12 hours, and the weight ratio of the solid mixture C, nano-alumina and sodium hydride is 100:(2-4):(5-12.5).
[0009] The preparation method of the above-mentioned carbon negative electrode material for sodium ion batteries comprises the following steps: subjecting coal powder to a roasting treatment with molten sodium bicarbonate and a hydrothermal treatment with a sodium hydroxide aqueous solution in sequence, thereby reducing metal impurities in the coal powder raw material, and combining nano-alumina and sodium hydride, and sintering treatment at 400 to 600° C. in an atmosphere of ethylene and an inert gas to obtain an alumina-coated carbon negative electrode material for sodium ion batteries, thereby improving the crystallinity and conductivity of the carbon negative electrode material for sodium ion batteries; improving the capacity and cycle performance of the carbon negative electrode material for sodium ion batteries, and having relatively excellent comprehensive performance.
[0010] Preferably, the weight ratio of the solid mixture C, nano-alumina and sodium hydride is 100:3:7.5-10.
[0011] When the weight ratio of the solid mixture C, nano-alumina and sodium hydride meets the above conditions, the crystallinity and conductivity of the carbon negative electrode material of the sodium ion battery are further improved; the capacity and cycle performance of the carbon negative electrode material of the sodium ion battery are improved, and it has better comprehensive performance.
[0012] Preferably, in step (1), the weight ratio of coal powder to sodium bicarbonate is 100:(10-15).
[0013] Preferably, in step (2), the concentration of the sodium hydroxide aqueous solution is 2-11 mol / L, and the ratio of the sodium hydroxide aqueous solution to the mixture A is 3-8 ml of the sodium hydroxide aqueous solution to 1 g of the mixture A.
[0014] Preferably, in step (4), the inert gas is nitrogen, helium, or argon. After the inert gas is introduced to replace oxygen, the flow rate of ethylene during the calcination process is 80 to 150 ml / min.
[0015] Preferably, in step (3), the solid mixture C is vacuum dried at 105-115° C. for 2-5 hours.
[0016] Preferably, in step (4), the maximum sintering temperature is 500-600°C. When the temperature is lower than 300°C, the temperature is increased to 300°C at a rate of 8-12°C / min, and then the temperature is increased to the above maximum sintering temperature at a rate of 1.5-2.5°C / min and kept at this temperature for 4-10 hours.
[0017] The present invention also provides a sodium ion battery carbon negative electrode material prepared by any of the above-mentioned methods for preparing the sodium ion battery carbon negative electrode material.
[0018] The present invention also provides a sodium ion battery carbon negative electrode material composition, comprising the above-mentioned sodium ion battery carbon negative electrode material, SP, CNT, CMC, SBR
[0019] The beneficial effects of the present invention are as follows: the present invention provides a sodium ion battery carbon negative electrode material and a preparation method and application thereof, and the present invention has the following advantages:
[0020] The present invention analyzes the relevant data in the material preparation process, optimizes the reaction conditions and preparation process, and thus makes the preparation method simpler and easier. Compared with the traditional method, the present invention has the following advantages:
[0021] 1. Low cost: Using common coal powder as raw material reduces the cost of material preparation.
[0022] 2. Optimized process: Sodium bicarbonate is used to activate coal powder, and sodium hydride and nano-alumina are used for sintering. The preparation steps are simple.
[0023] 3. It can improve the energy density and cycle life of sodium batteries, and reduce sodium loss and capacity degradation.
[0024] 4. Through alumina coating and sodium hydride treatment, the contact between electrolyte and alkaline solution and sodium is reduced, so as to reduce gas production, improve battery volume expansion, pole piece / diaphragm misalignment and other problems, and reduce battery life attenuation and safety issues.
[0025] 5. The process is simple, which is conducive to large-scale preparation. The preparation process is simple, suitable for industrial production, and can reduce production costs.
[0026] 6. Energy saving and emission reduction: Sodium bicarbonate activates coal powder, reducing the amount of subsequent alkali used; the sodium hydroxide solution used in the preparation process has a low concentration and the treatment process has less pollution; the sintering temperature is low and the energy consumption is low.
[0027] The method for preparing the carbon negative electrode material for a sodium ion battery of the present invention comprises the following steps: subjecting coal powder to a roasting treatment with molten sodium bicarbonate and a hydrothermal treatment with a sodium hydroxide aqueous solution in sequence, thereby reducing metal impurities in the coal powder raw material; and combining nano-alumina and sodium hydride, and sintering the mixture at 400 to 600° C. in an atmosphere of ethylene and an inert gas to obtain an alumina-coated carbon negative electrode material for a sodium ion battery, thereby increasing the crystallinity and conductivity of the carbon negative electrode material for a sodium ion battery; and improving the capacity and cycle performance of the carbon negative electrode material for a sodium ion battery. The carbon negative electrode material for a sodium ion battery of the present invention has relatively good comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM morphology structure diagram of the carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention.
[0029] Figure 2 This is a comparison of the carbon negative electrode material for sodium ion batteries according to an embodiment of the present invention, and the morphology of the aluminum oxide coating
[0030] Figure 3 This is the XRD diffraction pattern of the carbon negative electrode material of the sodium ion battery of the comparative example of the present invention.
[0031] Figure 4This is a battery performance diagram of the carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention.
[0032] Figure 5 The gas production of the slurry of the carbon negative electrode material for the sodium ion battery according to the embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0034] Example 1
[0035] A method for preparing a carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention comprises the following steps:
[0036] (1) coal powder and sodium bicarbonate were mixed in a weight ratio of 100:10, calcined in a muffle furnace at 300° C. for 60 minutes, and cooled to obtain a mixture A;
[0037] (2) Mixture A was crushed and then stirred in a 7.5 mol / L sodium hydroxide aqueous solution at 70° C. for hydrothermal reaction for 3 hours, wherein the liquid-to-solid ratio of mixture A to the sodium hydroxide aqueous solution was 4 mL / g; solid mixture B was collected after solid-liquid separation, and the solid-liquid separation method was vacuum filtration;
[0038] (3) washing the solid mixture B with deionized water until neutral, collecting the solid mixture C and drying it in vacuum at 105° C. for 4 hours;
[0039] (4) The solid mixture C is mixed with nano-alumina and sodium hydride and placed in a CVD furnace. The weight ratio of the solid mixture C, nano-alumina and sodium hydride is 100:3:7.5. Argon gas is introduced to replace the air. Ethylene is introduced at a gas flow rate of 100 mL / min. The mixture is sintered to obtain a carbon negative electrode material for a sodium ion battery. The sintering temperature is set to increase the temperature to 300°C at 10°C / min, then increase the temperature to 400°C at 2°C / min and keep it for 2 hours, then continue to increase the temperature to 500°C at 2°C / min and keep it for 6 hours, then continue to increase the temperature to 600°C at 2°C / min and keep it for 4 hours. The particle size of the nano-alumina is less than 1000 nanometers.
[0040] The elemental composition analysis of the solid mixture C(MX) after step (3) is as follows: Table 1
[0041] Table 1 Elemental composition analysis of the initial coal powder and the solid mixture C after treatment in step (3)
[0042]
[0043] Example 2
[0044] As a method for preparing a carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that: (1) the mixture A is crushed and then stirred in a 2.5 mol / L sodium hydroxide aqueous solution at 70° C. for hydrothermal reaction for 3 hours;
[0045] Example 3
[0046] As a method for preparing a carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that the weight ratio of the solid mixture C, nano-alumina, and sodium hydride is 100:3:5.
[0047] Example 4
[0048] As a method for preparing a carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that the weight ratio of the solid mixture C, nano-alumina, and sodium hydride is 100:3:10.
[0049] Example 5
[0050] As a method for preparing a carbon negative electrode material for a sodium ion battery according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that the weight ratio of the solid mixture C, nano-alumina, and sodium hydride is 100:3:12.5.
[0051] Comparative Example 1
[0052] As a method for preparing a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that step (2) is not included, and after step (1) is completed, steps (3) and (4) are directly performed.
[0053] Comparative Example 2
[0054] As a method for preparing a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that sodium hydride is replaced by sodium carbonate in step (4).
[0055] Comparative Example 3
[0056] As a method for preparing a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that in step (4), sodium hydride is not added, and the mass of sodium hydride is supplemented by nano-alumina.
[0057] Comparative Example 4
[0058] As a method for preparing a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that in step (4), no nano-alumina is added, and the mass of the nano-alumina is supplemented with sodium hydride.
[0059] Comparative Example 5
[0060] As a method for preparing a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that in step (4), nano-magnesium oxide is used to replace nano-aluminum oxide.
[0061] Comparative Example 6
[0062] As a method for preparing a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that in step (4), ethylene is replaced by methane.
[0063] Comparative Example 7
[0064] As a preparation method of a sodium ion battery carbon negative electrode material as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that the weight ratio of the solid mixture C, nano-alumina, and sodium hydride is 100:1:7.5.
[0065] Comparative Example 8
[0066] As a preparation method of a carbon negative electrode material for a sodium ion battery as a comparative example of the present invention, the only difference between this comparative example and Example 1 is that the weight ratio of the solid mixture C, nano-alumina, and sodium hydride is 100:3:2.5.
[0067] Comparative Example 9
[0068] As a preparation method of a sodium ion battery carbon negative electrode material as a comparative example of the present invention, the only difference between this comparative example and Example 1 is: (1) coal powder and sodium bicarbonate are mixed in a weight ratio of 100:5, and then calcined in a muffle furnace at 300° C. for 60 minutes, and then cooled to obtain a mixture A.
[0069] Comparative Example 10
[0070] As a method for preparing a carbon negative electrode material for a sodium ion battery according to Example 1 of the present invention, the only difference between this embodiment and Example 1 is that the weight ratio of the solid mixture C, nano-alumina, and sodium hydride is 100:5:7.5.
[0071] The preparation method parameters of Examples 1 to 5 and Comparative Examples 1 to 10 are shown in Table 1.
[0072] Table 1 Parameters of the preparation method of carbon negative electrode materials for sodium ion batteries
[0073]
[0074]
[0075] 1. Samples to be tested
[0076] The sodium ion battery carbon negative electrode material was prepared according to the preparation method of the sodium ion battery carbon negative electrode material of Examples 1-5 and Comparative Examples 1-10, and the material was prepared as a sample according to the addition amount of 5g of the raw material.
[0077] 2. Detection Method
[0078] (A) Crystallinity detection.
[0079] Figure 3 XRD diffraction patterns and crystallinity measurements of Example 1 and Comparative Example 4.
[0080] Table 2 Crystallinity of carbon negative electrode materials for sodium ion batteries
[0081] Characteristic peak Height FWHM Crystallinity Example 1 652.2 0.426 85.46% Comparative Example 4 239.1 1.831 80.22%
[0082] Crystallinity calculation formula (XRD diffraction method):
[0083] Crystallinity = (Icr / Iam)*100%
[0084] Where Icr is the crystallization peak intensity
[0085] Iam is the non-crystalline peak intensity
[0086] The SEM electron microscope picture of Example 1 is as follows Figure 1 As shown, it can be seen that the carbon negative electrode material has a layered structure and the alumina coating layer is uniform;
[0087] Figure 2 (a) Figure 2 (b) Figure 2 The SEM images of (c) are respectively Comparative Example 7, Example 1, and Comparative Example 10. It can be seen that the aluminum oxide coating layer of Comparative Example 7 is too thin and uneven, and the aluminum oxide coating layer of Comparative Example 10 is too thick, which affects the electrical properties of the material;
[0088] Figure 4 The cycle performance of Example 1, Comparative Example 1 and Comparative Example 3 is compared.
[0089] (II) Battery performance testing
[0090] Battery Performance
[0091] The crystallinity and battery performance results of the sodium ion battery carbon negative electrode materials of Examples 1-5 and Comparative Examples 1-10 are shown in Table 3.
[0092] Table 3 Crystallinity and battery performance of carbon negative electrode materials for sodium ion batteries
[0093] (III) Gas production detection
[0094] The prepared sodium ion battery carbon negative electrode material is assembled into a button battery, specifically with a button battery formula of 0.288gSP+3gCNT+8.1282gCMC glue+5.4g sodium ion battery carbon negative electrode material+0.525gSBR, premixed for 3min at 200r / min in a centrifugal degassing machine, mixed for 10min at 1000r / min, and then vacuum degassed for 5min to prepare a coating slurry, a certain amount of slurry is placed in an aluminum-plastic film bag, and the vacuum packaging machine is packaged after exhausting the gas, and the gas production is observed every 8h, and the volume change of the aluminum-plastic film bag after gas production and deformation is calculated by the drainage method, and the volume of the initial slurry after the aluminum-plastic film bag is exhausted is 20.0ml;
[0095] Figure 5 In the case of bubbles in the slurry, Figure 5 a is Example 1, Figure 5 b is comparative example 4, and the gas generation of the slurry will affect the safety performance of the battery material.
[0096] Table 3 Battery performance results of carbon negative electrode materials for sodium ion batteries
[0097]
[0098]
[0099]
[0100] As can be seen from Table 3, the preparation method of the carbon negative electrode material for a sodium ion battery of the present invention is to subject the coal powder to a roasting treatment with molten sodium bicarbonate and a hydrothermal treatment with an aqueous sodium hydroxide solution in sequence, thereby reducing metal impurities in the coal powder raw material, and combining nano-alumina and sodium hydride, and sintering treatment at 400 to 600° C. in an atmosphere of ethylene and an inert gas to obtain an alumina-coated carbon negative electrode material for a sodium ion battery, thereby improving the crystallinity and conductivity of the carbon negative electrode material for a sodium ion battery; and improving the capacity and cycle performance of the carbon negative electrode material for a sodium ion battery. As can be seen from Tables 2 and 3, the carbon negative electrode material for a sodium ion battery of the present invention has better comprehensive performance.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon negative electrode material for a sodium ion battery, characterized in that: The preparation method comprises the following steps: (1) mixing coal powder and sodium bicarbonate, calcining the mixture in a muffle furnace at 270° C. to 350° C. for 60 to 120 minutes, and cooling the mixture to obtain a mixture A; (2) mixing the mixture A in a sodium hydroxide aqueous solution at 65 to 80° C. and stirring to react for 1.5 to 4 hours, collecting the solid mixture B after solid-liquid separation, and the concentration of the sodium hydroxide aqueous solution is not less than 2 mol / L; (3) washing the solid mixture B with deionized water until it is neutral, collecting the solid mixture C and drying it; (4) After mixing the solid mixture C with nano-alumina and sodium hydride, sintering the mixture in an atmosphere of ethylene and inert gas to obtain a carbon negative electrode material for a sodium ion battery. The maximum sintering temperature is 400-600° C., the insulation time is 4-12 hours, and the weight ratio of the solid mixture C, nano-alumina and sodium hydride is 100:(2-4):(5-12.5).
2. The method for preparing the carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: The weight ratio of the solid mixture C, nano-alumina and sodium hydride is 100:3:7.5-10.
3. The method for preparing the carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step (1), the weight ratio of coal powder to sodium bicarbonate is 100:(10-15).
4. The method for preparing the carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step (2), the concentration of the sodium hydroxide aqueous solution is 2-11 mol / L, and the ratio of the sodium hydroxide aqueous solution to the mixture A is 3-8 ml of the sodium hydroxide aqueous solution to 1 g of the mixture A.
5. The method for preparing the carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step (4), the inert gas is nitrogen, helium, or argon. After the inert gas is introduced to replace oxygen, the flow rate of ethylene during the calcination process is 80 to 150 ml / min.
6. The method for preparing the carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step (3), the solid mixture C is vacuum dried at 105-115° C. for 2-5 hours.
7. The method for preparing the carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: In step (4), the maximum sintering temperature is 500-600°C. When the temperature is lower than 300°C, the temperature is increased to 300°C at a rate of 8-12°C / min, and then the temperature is increased to the above maximum sintering temperature at a rate of 1.5-2.5°C / min and kept at this temperature for 4-10 hours.
8. A sodium ion battery carbon negative electrode material prepared by the method for preparing a sodium ion battery carbon negative electrode material according to any one of claims 1 to 7.
9. A sodium ion battery carbon negative electrode material composition, comprising the sodium ion battery carbon negative electrode material as claimed in claim 8, conductive carbon black, carbon nanotubes, carboxymethyl cellulose and styrene-butadiene rubber.
Citation Information
Patent Citations
Battery positive electrode material, positive pole plate comprising same, battery negative electrode material, negative pole plate comprising battery negative electrode material, lithium ion battery and electrode paste
CN110212182A
Low-crystallization-degree coating material and preparation method thereof, anode material and lithium battery anode
CN111785915A
Netted gamma-aluminum oxide coated modified graphite negative electrode material as well as preparation method and application thereof
CN113363445A
Preparation method and application of nitrogen-doped porous carbon material based on medium-rank coal
CN113793942A
Novel aluminum-carbon coated graphite negative electrode material for lithium ion battery and preparation method of novel aluminum-carbon coated graphite negative electrode material
CN114975966A